The eroticization of Tibetan monks in shōnen-ai and yaoi manga. Issue 1 (7th March 2023) - Christopher, Stephen; Laumonier, Gabrielle
Men have historically dominated the artistic production of cultural exotifications. This article flips the script by analysing how two prominent female Japanese manga artists – Kuranishi and Shinsan Nameko – erotically illustrate Tibetan men, specifically Tibetan Buddhist monks. Through textual analysis and fieldwork conducted between 2019 and 2021, we show how their manga depictions of Tibetan young men, in particular monks, tend towards eroticization and sexual innuendo. This discursive and aesthetic trend in manga parallels ethnographic data on how Japanese women – facing unprecedented social precarity, seeking spiritual healing and self-transformation and desiring alternate masculinities – look elsewhere, outside of Japan and the perceived inadequacies of Japanese masculinities. We explore how liberative erotics, especially homoeroticism and love between boys, fuses with Buddhist and alternative spiritualities in yaoi and shōnen-ai genres and gestures towards a changing landscape of female desire.